Valorização da poda da vide e da casca da castanha: pré-tratamento e hidrólise enzimática da celulose - Maciel, Tatiane Cavalcante (2017)
The lignocellulosic biomass represents the carbon source renewable most abundant in the world, being constituted by polymers of lignin, hemicellulose and cellulose. In the last yeares, these materials has received more attention because are rich in sugars and most part they are residues from other production processes. For this reason, the numbers of researches with the objective of fractionate them and apply their constituents in the production of products high added value has grown in around the world. The sugars released from biomass can be employed as carbon source, in the production of antibiotics, amino acids, enzymes and biochemicals as biofuels.The fractionate of the biomass occurs through pretreatments that can to be chemical, phisical, phisical-chemical and biological. Because of complexity these materials there is no single pretreatment that are equally efficient for all them. Therefore, studies to check which the treatment most indicated for the each material or for a specific application must be performed. In this work, two residues, the vine pruning and chestnut shell were selected. The objective was to define the best conditions for to remove hemicellulose and lignin in these materials, and the residues treated were hydrolyze with commercial enzymes Cellic® CTec2 e Novozyme 188 in order to assess the efficacy of the processes. In the delignification, among conditions tested, the higher removal of lignin (63.8%) occurred in the material treated with 3.0% of NaOH and 120 ºC (without agitation during 60 minutes). However, the most yield in glucose was obtained from enzymatic hydrolysis of the vine pruning treated with 2.0% of NaOH and 100 ºC (without agitation during 60 minutes). It could be concluded that do not always the material with lower content of lignin result in higher yields in glucose. The chestnut shell was the other residue utilized in this work. It was subbmited only the delignification with NaOH in differents combinations of temperature and concentration. In the assay performed at 100 ºC with 2.0% of NaOH under agitation, the lignin was almost completely removed (94.3%). The lower amount of lignin (75%) removal with treatments occured when the material was subbmited at 1.0% NaOH, 60 ºC during 1 hour. Therefore, the materials obtained in all conditions were subjected at enzymatic hydrolysis with commercial enzymes. The yields quantified in glucose after 72 hours of hydrolysis not showed difference significative in accordance Tukey’s test. For this reason, the treatment performed with 1.0% of NaOH and 60 ºC was chosen. With these results was to possible that confirm the importance of the enzymatic hydrolysis data in the evaluation of efficiency of lignocellulosic material pretreatment, because not always the conditions that removed the highest quantify of lignin or hemicellulose are the most interesting. Depending on the change occured in material and the enzymes employed, the mild conditions may provide satisfactory performance. The results obtained by the classical analysis recommended by NREL were corroborated by eletronic microscopy in which it is clearly shown the lignin removal and the exposure of the internal vegetal cell structure in the biomass.